Analysis of Traffic Accident Characteristics Using The Ean (Accident Equivalent Number) Method of The Case Study Narogong Road in Bekasi - Rifai, Andri Irfan; Sopiyan, Yopi (Journal of World Conference (JWC), 2020)
This study uses the Accident Equivalent Number (EAN) method based on the weighted value of accident victims with the accident fatality rate and the number of victims. The weighting of the accident rate is then determined by the EAN formula: 12MD + 3LB + 3LR + 1K, then using the Upper Control Limit (BKA) formula to determine the ranking of accident-prone points with the formula BKA = C + 3?C to determine priority handling of accident-prone points. And using the road inventory survey method to find out the factors that cause accidents and efforts to handle accident-prone points appropriately Based on the results of the analysis it can be concluded that the Narogong road in the city of Bekasi is classified as an accident-prone area because it has an EAN value that exceeds the Upper Control Limit (BKA) value. The coordinate point of the location with the highest EAN value is segment three at the point -6.3145869 s.d '-6.3230043. (residential area of ??Vida Bekasi to Bantar Gebang market area) with an EAN value of 126 and a BKA value of 48.3. In this segment there have been 12 accidents with 7 fatalities, 2 seriously injured, 8 slightly injured with a material loss of Rp. 11,200,000. And the dominant type of accident is the front-rear hit-and-hit accident by 39% with the cause of the traffic accident being the driver factor by 76%. Efforts to handle accident-prone points by holding counseling about safety riding, painting road markings, installing road signs as needed, and conducting routine checks of street lighting that is not functioning.